Advancing Health Equity With Lifestyle Medicine. Issue 6 (November 2018) - Rooke, Jennifer
The Optimal Health and Wellness Clinic of Morehouse Healthcare seeks to advance health equity by providing lifestyle medicine services to its predominantly African American patient population. Health equity means eliminating health disparities by providing services that meet the needs of the population served. African Americans have a higher burden of cardiovascular disease and diabetes than other American ethnic groups. Recent evidence indicates that eating a plant-based diet may eliminate disparities in cardiovascular disease and diabetes. The clinic provides lifestyle intervention services such as stress and sleep management, but the focus is on helping patients to adopt and maintain a plant-based diet. A range of encounter options that include shared medical appointments and cooking classes are offered. The clinic is an example of a lifestyle medicine specialty practice within the multispecialty practice arm of a medical school. The shared mission to promote health equity provides substantial resources to the clinic and allows for collaborative efforts to improve the health of the community.